2001
DOI: 10.1094/mpmi.2001.14.7.832
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Genes Mediating Enhanced Fungal Resistance in Transgenic Wheat

Abstract: Three cDNAs encoding the antifungal protein Ag-AFP from the fungus Aspergillus giganteus, a barley class II chitinase and a barley type I RIP, all regulated by the constitutive Ubiquitin1 promoter from maize, were expressed in transgenic wheat. In 17 wheat lines, stable integration and inheritance of one of the three transgenes has been demonstrated over four generations. The formation of powdery mildew (Erysiphe graminis f. sp. tritici) or leaf rust (Puccinia recondita f. sp. tritici) colonies was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 37 publications
4
73
0
Order By: Relevance
“…The transformation efficiency obtained in our study (2%) was similar to that observed in wheat by Vasil et al (1993), Oldach et al (2001) and MacKintosh et al (2006). However this efficiency might be considered a limitation if the study of many transgenes is tackled with limited operational capacity (Dahleen et al 2001).…”
Section: Discussionsupporting
confidence: 80%
“…The transformation efficiency obtained in our study (2%) was similar to that observed in wheat by Vasil et al (1993), Oldach et al (2001) and MacKintosh et al (2006). However this efficiency might be considered a limitation if the study of many transgenes is tackled with limited operational capacity (Dahleen et al 2001).…”
Section: Discussionsupporting
confidence: 80%
“…This high level of basal non-specific resistance was found to be associated with the upregulation of two chitinases, three b-1,3-glucanases and four osmotins. Transgenic plants overexpressing chitinase alone or in combination with b-1,3-glucanase have been previously shown to display an enhanced resistance when challenged with a powdery mildew infection (Oldach et al, 2001) or bacterial pathogens (Dana et al, 2006). Delayed symptoms of Fusarium head blight have also been reported in these transgenic plants (Anand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such promoters are typically dysfunctional in cereal species. Thus, expression of transgenes in cereals has been largely driven by ubiquitous promoters, such as those from the maize (Zea mays) ubiquitin 1 (Ubi1; Christensen et al, 1992;Oldach et al, 2001) or the rice (Oryza sativa) actin 1 gene (Act1; McElroy et al, 1990;Vickers et al, 2006). However, a few specific promoters derived from cereal species have been characterized and used to drive transgene expression.…”
mentioning
confidence: 99%